Oncological safety of selective axillary dissection after axillary reverse mapping in node-positive breast cancer. Issue 7 (July 2021) - Gennaro, Massimiliano; Listorti, Chiara; Mariani, Luigi; Maccauro, Marco; Bianchi, Giulia; Capri, Giuseppe; Maugeri, Ilaria; Lozza, Laura; De Santis, Maria Carmen; Folli, Secondo
Abstract: Introduction: Although the need for axillary lymph node dissection (AD) is decreasing in breast cancer patients, it remains necessary in some cases. Axillary reverse mapping (ARM) enables the detection of upper extremity lymphatic drainage that may be spared during selective axillary dissection (SAD) so as to reduce the risk of lymphedema. The ability of the ARM-SAD procedure to reduce the incidence of lymphedema is being tested in an ongoing randomized trial. Crossover between arm drainage and breast drainage is well documented in the axilla, however, and whether the procedure is oncologically safe remains controversial. We aim to assess the axillary failure rate when a few nodes draining the upper arm are being spared by the ARM-SAD. Methods: We report oncological outcomes, and axillary failure in particular, in the first 100 consecutive axillary node-positive patients treated with ARM-SAD as part of a pilot study and a randomized trial. Results: A median of 18 (IQR 14–22) axillary nodes were excised per patient. During the follow-up (median 51 months, IQR 34–91), 11 patients experienced a treatment failure, but only one - treated with neoadjuvant chemotherapy - developed overt axillary disease as a first (and isolated) event. The crude rate of axillary failure was 1.36% (95% CI: 0.19–9.63) with an estimated 5-year crude cumulative incidence of 1.85% (95% CI: 0–5.47%). Conclusions: The axillary failure rate was low in our patients and did not exceed rates reported in the literature after standard AD, thus indicating that the ARM-SAD procedure is oncologically safe.